(untitled) (Scientific journal of the Fergana State University, 2023)
This article analyzed the sociopragmatic features of military phraseological units in the German language. According to the structure of military phrases, they are equivalent to a phrase and a sentence. Military expressions were divided into groups of positive, negative, neutral and evaluative relations in terms of form and content as a linguistic unit. Simplicity, impressiveness, elation, magnificence, freedom were identified in the phraseological units expressing the evaluation attitude specific to the style of colloquial speech. Military phraseological units are language units that express a strong, figurative, emotional-expressive meaning, and in order to understand their connotation, the meaning of phraseological units was compared with the semantics of the corresponding words. Also, the pragmatic functions of military phraseological units are shown and illustrated in examples.